Civilizar o campo: educação e saúde nos cursos de aperfeiçoamento para professores rurais - Fazenda do Rosário (Minas Gerais, 1947-1956) - Larissa Assis Pinho (2009)
The objective of this dissertation is to understand the implementation of a pedagogic proposal of rural education in the teachers' formation courses, carried out in Minas Gerais in the middle of the century XX. Taking as a focus the analysis of the Courses of Improvement for rural teachers which took place in the Fazenda do Rosário (Ibirité, Minas Gerais) between the years of 1948 and 1956, there was identified the constitution of a differentiated proposal of education for the rural environment, which has been denominated as rural pedagogy. The rural pedagogy refers to a set of propositions and reflections about the teaching methodology and of school and educative practices to be developed in the rural elementary schools, substantiated by a conception of education and of school in an specific geographical and population environment, although the inspiration is of the pedagogy in development in the city. In this period, the differential of the pedagogic ideas for the rural area was the proposal of urbanization of the field and civilization of its population, through the school and the acting of the primary teacher. Investing in the improvement of the conditions and the quality of life of the population from the rural area involved developing the education and the health, which was articulated mainly in the context of the hygienist practices of the courses of teachers' formation. The "reform" of the rural man included the education of his bodies, aiming the hygienization of the habits and of the customs of this population. In the methodological aspect, more specific bibliographical studies were carried out on the history of the rural education, and more general studies referring to the sociological discussions on the rural and urbane categories, as well as on the imaginary about the social and historical conditions that constitute the symbolic dimensions of the rural one and of the urbane one. Different documentary sources were consulted: legislation, reports and official documents, newspapers, magazines, books and collections, and documentary heap of the Centre of Documentation and Researches Helena Antipoff (texts and reports; diaries and individual notebooks; questionnaires carried out with the teachers; release of registers of enrolment of pupils and of teachers). It can be concluded that the educative proposals of the courses of teachers' formation of the Fazenda do Rosário were developed in communion with the sociological discussion of that time, which was constituted by the overcoming of the rural way by the urbane one. It is observed, however, that the implementation of the proposals of education in the rural environments did not do itself without tensions. Tensions and contradictions that permeated the pedagogic ideas for the rural way and the concrete conditions for intervention of it, as much as the expectations of the rural population itself regarding the improvements of their conditions and ways of life .